PENGARUH PENGUKUSAN DAN PERAJANGAN DAUN GAMBIR (Uncaria gambir ROXB) TERHADAP MUTU EKSTRAK GAMBIR - Zulnely Zulnely; Abdul Hakim Lukman (Jurnal Penelitian Hasil Hutan, 1994)
This experiment is 10 study the effect of steaming duration and chopping sizes of gambier leaves (Uncaria gambir ROXB) on both yield and quality.The steaming duration of the samples were conducted at 30,40, 60 and 75 minutes  and tire chopping sizes of tire sample consisted of  0.5-1  cm,  2-3 cm,  4-6 cm,  and unchopping,  The results were analyzed  using the factorial  design  with two replicates and the difference between means were tested with multiple range Duncan "s test.The results showed than the steaming duration and the chopping sizes had a significant  effect on  the yield,  catechin  consent, insoluble matter and insoluble matter in alcohol.  Combination of 0.5-1 cm     chopping size and 30 minutes steaming duration was the best treatment.  This combination produced  10.34  % yield of gambier ext. act,  75.82%  catechin content,  11.34 % moisture content, 4.75 % ash content,  4.86  % insoluble matter, and 12.03 % insoluble matter in alcohol.